Peg + Cat. Peg rocks! [videorecording (DVD)] ([Publisher not identified], 2015)
Fun ensues when Peg and Cat need to round up the missing members of their touring band in time for their big gig performing for 100 chickens, hit the mall to join the Zebra Guy dance contest, and hit some wrong notes when they get stuck in a spectacular instrument built from junk. Includes 7 rockin' stories!